Louis-Joseph Janvier and “The Detractors of The Black Race”: An Anthropological Critique - Frantz Rousseau Déus (Vibrant: Virtual Brazilian Anthropology, 2024)
Abstract Ideas of hierarchy, inferiority and racial inequality predominated in the work of certain European intellectuals of the 18th and 19th centuries on the idea of ‘races’. The Société d’Ethnologie de Paris (SEP) and the Société d’Anthropologie de Paris (SAP) are two French institutions that had intellectuals who participated in the consolidation of these conceptions. Since the 18th century there have been criticism by black intellectuals; however, with the emergence of the First Black Republic of the modern era in Haiti, these criticisms gained new contours. Many Haitian intellectuals in the first and second half of the 19th century dedicated themselves to combating hierarchical ways of thinking, demonstrating their inconsistencies. In this article, based on bibliographical research, we consider the anthropological work of the Haitian Louis-Joseph Janvier (1855-1911), highlighting his contribution to struggles toward deconstructing the imaginary of racial inferiority attributed to black people and used to legitimize their domination and exploitation. Discussing the racial issue in Janvier’s thinking is relevant as it continues to be a dilemma and a challenge in the contemporary world.